Pengaruh Media Pembelajaran Kahoot terhadap Hasil Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Kelas 8 di MTs Pui Kuningan - Lusiana, Ega Maigita; Gustiana, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study is based on the low level of student engagement and unsatisfactory learning outcomes due to the continuous application of conventional teaching methods. The purpose of this research is to analyze the effect of using Kahoot as a learning tool on the learning outcomes of eighth-grade students at MTs PUI Kuningan in the Indonesian Language subject. The method used is a one-group pretest-posttest design with a quantitative approach. The sampling technique used was total sampling, 19 students from class 8 at MTS Kuningan were used as research samples. Data collection procedures included questionnaires, tests (pretest and posttest), and observations. Data were analyzed using descriptive statistics, normality testing, N-Gain analysis, and hypothesis testing with Paired Sample T-Test. The findings from the N-Gain test indicate an increase in student learning outcomes after using Kahoot, which is categorized as effective. In addition, the analysis shows a significant difference between the pretest and posttest scores, as reflected by the t-test significance value which is below 0.05. The results obtained in this study confirm that Kahoot is an effective tool for improving student learning outcomes and offers a fun and interactive alternative compared to conventional language teaching methods, especially in learning Indonesian.